SlMYB75, an MYB-type transcription factor, promotes anthocyanin accumulation and enhances volatile aroma production in tomato fruits. Issue 1 (1st February 2019) - Jian, Wei; Cao, Haohao; Yuan, Shu; Liu, Yudong; Lu, Juanfang; Lu, Wang; Li, Ning; Wang, Jianhui; Zou, Jian; Tang, Ning; Xu, Chan; Cheng, Yulin; et al.
Abstract: Genetic manipulation of genes to upregulate specific branches of metabolic pathways is a method that is commonly used to improve fruit quality. However, the use of a single gene to impact several metabolic pathways is difficult. Here, we show that overexpression of the single gene SlMYB75 ( SlMYB75 -OE) is effective at improving multiple fruit quality traits. In these engineered fruits, the anthocyanin content reached 1.86 mg g −1 fresh weight at the red-ripe stage, and these SlMYB75 -OE tomatoes displayed a series of physiological changes, including delayed ripening and increased ethylene production. In addition to anthocyanin, the total contents of phenolics, flavonoids and soluble solids in SlMYB75 -OE fruits were enhanced by 2.6, 4, and 1.2 times, respectively, compared to those of wild-type (WT) fruits. Interestingly, a number of aroma volatiles, such as aldehyde, phenylpropanoid-derived and terpene volatiles, were significantly increased in SlMYB75 -OE fruits, with some terpene volatiles showing more than 10 times higher levels than those in WT fruits. Consistent with the metabolic assessment, transcriptomic profiling indicated that the genes involved in the ethylene signaling, phenylpropanoid and isoprenoid pathways were greatly upregulated in SlMYB75 -OE fruits. Yeast one-hybrid and transactivation assays revealed that SlMYB75 is able to directly bind to the MYBPLANT and MYBPZM cis -regulatory elements and to activate the promoters of the LOXC, AADC2 and TPS genes. The identification of SlMYB75 as a key regulator of fruit quality attributes through the transcriptional regulation of downstream genes involved in several metabolic pathways opens new avenues towards engineering fruits with a higher sensory and nutritional quality. Genetics: one small tweak, one giant leap for tomatoes: A single gene has been identified in tomatoes that regulates multiple aspects of fruit quality, including levels of health-promoting anthocyanins, opening the door to engineering more nutritious and better-tasting tomatoes. Fruit breeders have long-manipulated genes to enhance traits like yield or disease resistance, but it is rare to find a single gene that can improve multiple aspects of fruit quality. In this study, Zhengguo Li at Chongquing University in China and colleagues show that over-expressing a transcription factor called SIMYB75 results in striking deep purple tomatoes enriched in anthrocyanins–antioxidants thought to be protective against various diseases - which tomatoes are usually devoid of. They also had higher levels of other health-promoting phytochemicals and enhanced production of aroma volatiles, which can influence the taste and flavor of fruit.